2010
DOI: 10.1163/156920810x529958
|View full text |Cite
|
Sign up to set email alerts
|

How do Qatari Females Make it to the Top? An Examination of the Organizational Constraints to their Advancement

Abstract: Although Qatari females have increased their economic participation and reached remarkable educational attainment over the last decade, this has not been paralleled with good representation at management position. Accordingly, this study was initiated with the aim to identify the main organizational constrains encountered by Qatari females throughout their careers. The study revealed that Qatari females are still very lowly representated at senior management levels although they have made good progress at medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…They also emphasized the importance of religion and family in their lives. Similar to previous studies (Al Muftah, 2010), 15 of the participants believed that families played a crucial role as gatekeepers to access resources facilitated by the government. Additionally, the study found that age was directly proportional to the power held by these women.…”
Section: Methodssupporting
confidence: 78%
“…They also emphasized the importance of religion and family in their lives. Similar to previous studies (Al Muftah, 2010), 15 of the participants believed that families played a crucial role as gatekeepers to access resources facilitated by the government. Additionally, the study found that age was directly proportional to the power held by these women.…”
Section: Methodssupporting
confidence: 78%
“…Yet, social structure is fabricated with cultural constraints (i.e. the household division of labor, family structures and gender roles within households and societal barriers to traditionally male-dominated sectors) trigger concern about hindering gender equity in political authority and decision-making roles (Al Ghanim, 2008; Al Muftah, 2010; Crabtree, 2007) at the national, societal, and family levels, especially in conservative contexts (Thompson, 2015) within the Arab Gulf transitional societies.…”
Section: Resultsmentioning
confidence: 99%
“…There is, however, a notable absence of women in senior management roles and political authority positions (Al Muftah, 2010) due to the social structure that is fabricated into a patriarchal system (i.e. based on a hierarchy of authority governed and regulated by men), thereby creating sociocultural constraints (Said-Foqahaa and Maziad, 2011).…”
Section: Introductionmentioning
confidence: 99%